EFEKTIVITAS PEMBELAJARAN MENGGUNAKAN PERMAINAN TRADISIONAL TERHADAP MOTIVASI DAN HASIL BELAJAR MATERI GAYA DI KELAS IV MIN NGRONGGOT NGANJUK - Ilza Ma’azi Azizah (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2016)
Kasti is traditional games such as baseball games for students of primary schools/ madrasah, this is important because Kasti can develop the physical and psychological aspects of students. In the physical aspect, the game roundersable to make students more active in learning activities. Physical activeness contained in such games can be used to study the concept of stylish materials, whereas the psychological aspect, an element of fun baseball game. In the course of learning, pleasant atmosphere will affect the student’s motivation to learn, so it can have an impact on improving student learning outcomes. The purpose of this study is the first, to explain the effectiveness of learning using traditional games on motivation to learn. Based on the research, we concluded that, on the variable of learning motivation, learning application using the traditional game is more effective in increasing student motivation than learning without the traditional game.Kata Kunci: Permainan Tradisional, Kasti, Motivasi.